(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Currently, indigenous peoples are going through a social and health crisis, in which their rights have been subjugated, leading to constant encroachments on their lands, protected by law. These invaders also prevent government aid, which brings the aggravation of endemic diseases in the regions, in addition to the lack of resources, such as food and drinking water. In view of the above, the objective is to understand how the arrival of Europeans and their relations with the natives fosters neglect and prejudice towards the indigenous peoples in modern times. For this, the methodology of bibliographic review and documentaries that address the theme was used. In addition, it sought to analyze concrete cases, such as the murder of Dom and Bruno, complaints to the State, such as the one made by the United Nations High Commissioner for Human Rights, in addition to norms that deal with the subject. The research showed that prejudice is structural, originating from the domination of the Portuguese in Brazil and continuing to this day. In addition, it is shown that although the country has a chance to react, whether in accordance with the actions of government representatives or society itself, With visible and possible solutions, it is not yet possible to verify significant and necessary actions. Thus, it is concluded that the Brazilian State has been omitting its functions and obligations, while the decimation of the remaining indigenous peoples, those who have a rich culture and ethnicity to add to the country, passes in front of them.